The role of manual occupation in the aetiology of Dupuytren's disease in men in England and Wales. - Khan, A; Rider, O; Jayadev, C; Heras-Palou, C; Giele, H; Goldacre, M (2004)
We compared the incidence of significant Dupuytren's disease in men across occupational social classes in England and Wales, using data from the National Morbidity Survey. We found that manual occupational social class was not associated with an increased incidence of Dupuytren's disease. In fact, the incidence rates of Dupuytren's disease in the elderly were higher in non-manual than in manual social classes.